2019
DOI: 10.3390/pharmaceutics11060254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fugitive Aerosols Released into the Environment during High-Flow Therapy

Abstract: Background: Nebulised medical aerosols are designed to deliver drugs to the lungs to aid in the treatment of respiratory diseases. However, an unintended consequence is the potential for fugitive emissions during patient treatment, which may pose a risk factor in both clinical and homecare settings. Methods: The current study examined the potential for fugitive emissions, using albuterol sulphate as a tracer aerosol during high-flow therapy. A nasal cannula was connected to a head model or alternatively, a int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 39 publications
3
46
0
1
Order By: Relevance
“…At a distance of 0.8 m from the ventilator, higher aerosol mass concentrations were found consistently for each measurement compared to the 2.0 m distance, in line with previous studies (McGrath et al, 2019a;McGrath et al, 2019b). Interestingly, when comparing Figs.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…At a distance of 0.8 m from the ventilator, higher aerosol mass concentrations were found consistently for each measurement compared to the 2.0 m distance, in line with previous studies (McGrath et al, 2019a;McGrath et al, 2019b). Interestingly, when comparing Figs.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…These studies focused on a visual approach and did not obtain quantitative data regarding fugitive emissions. Recent studies have proceeded to quantify aerosol mass concentrations of fugitive emissions from various nebulisers and patient interfaces including; facemasks, mouthpiece combination, nasal cannula and tracheostomy reporting mass fugitive emissions as high as 0.370 ± 0.046 mg m −3 (Elmashae et al, 2019;McGrath et al, 2019a;McGrath et al, 2019b;Oilier et al, 2019). It is evident from these studies that aerosol is emitted into the surrounding environment when a patient undergoes respiratory therapy, and secondary exposure is a factor for HCWs and bystanders to consider.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The non-deposited, exhaled dose, however, can be a significant health hazard in both clinical and homecare settings. In two publications, McGrath and colleagues used nebulised albuterol sulphate solution when they investigated fugitive aerosol emissions from two commercially available nebulisers in combination with an open or valved facemask or using a mouthpiece with and without a filter [ 20 ] and during high flow nasal cannula (HFNC, see below for more on HFNC) therapy [ 21 ], respectively. It was shown that the MMAD of the fugitively-emitted aerosols was less than 1 µm, while the initially generated aerosols were between 2 and 5 µm.…”
Section: Environmental Exposure and Toxicity Studiesmentioning
confidence: 99%
“…Several recent studies highlight the risks, the differences between devices, and the steps that can be taken to reduce the risk of unintended inhalation of fugitive emissions. Briefly, the guidance is that closed-circuit nebulizer systems, such as vibrating mesh nebulizers, should be used, and open circuit nebulizer systems, such as jet nebulizers that require a break in the patient circuit should be avoided [ 106 , 107 , 108 , 109 , 110 ].…”
Section: Routes Of Administration For the Treatment Of Respiratorymentioning
confidence: 99%